BIN1 K358R variant in 5xFAD mice ameliorates AB pathology and microgliosis. (20th December 2022) - Tran, Katelynn; Milinkeviciute, Giedre; Tran, Kristine M; Phan, Jimmy; Da Cunha, Celia; Javonillo, Dominic I; Kawauchi, Shimako; Tenner, Andrea J; LaFerla, Frank; MacGregor, Grant R; Green, Kim N
Abstract: Background: Genome‐Wide Association Studies (GWAS) identified bridging integrator 1 (BIN1) as the most important susceptibility loci for late‐onset Alzheimer's disease (LOAD), second to apolipoprotein E (APOE). BIN1 is an important regulator of endocytosis and membrane dynamics. Neuronal BIN1 localizes to pre‐synaptic termini where it functions in excitatory synaptic transmission via regulation of neurotransmitter vesicle dynamics. In humans, the gene produces multiple isoforms with 7 brain specific isoforms. A missense variant in Bin1 (K358R) has been linked to increased risk of development of LOAD. Here, we introduced this variant in mice and evaluated its effects on plaque genesis and subsequent damage. Method: To create the Bin1K358R allele, CRISPR/Cas9 endonuclease‐mediated genome editing of Bin1 was used to introduce a K426R mutation. This mutant allele models a SNP (rs138047593) found in human BIN1 that encodes a missense mutation associated with increased risk of sporadic Alzheimer's disease. The K358R variant in human BIN1 (K542R in the BIN1‐202 isoform) is located within the C‐terminal SH3 domain. Generated BIN1 K358R mice were crossed with 5xFAD mouse models, creating four groups (wild type (WT), BIN1K358R homozygous (HO), 5xFAD, and 5xFAD/BIN1 K358R HO), then aged to 4 months for analysis of AD‐related pathology. Coronal brain sections were immunolabeled to visualize dense‐core plaques (Thioflavin‐S), microglia (IBA1), reactive astrocytes (GFAP), axonal and neuritic damage (neurofilament light chain (NfL) and LAMP1, respectively). Confocal images of hippocampal and cortical regions were analyzed using Imaris software. In addition, Aβ and NfL levels were quantified in the brain tissue and plasma NfL measured using Meso Scale Discovery technology. Result: BIN1 K358R introduced in the 5xFAD background significantly reduces plaque densities and associated microgliosis in the hippocampal region, which matches insoluble Aβ42 levels. In contrast, GFAP levels are significantly increased in 5xFAD/BIN1 K358R mice compared to 5xFAD mice. Despite reduced plaque densities, dystrophic neurite area as measured by LAMP1 staining, as well as plasma NfL, are equivalent between 5xFAD/BIN1 K358R and 5xFAD mice, suggesting increased damage per plaque. Conclusion: BIN1 K358R reduces Aβ plaque deposition, but exacerbates the damage caused by those plaques, as determined by the surrounding halo of dystrophic neurites, and plasma NfL.